Rear-facing versus forward-facing child restraints: an updated assessment. Issue 1 (25th November 2017) - McMurry, Timothy L; Arbogast, Kristy B; Sherwood, Christopher P; Vaca, Federico; Bull, Marilyn; Crandall, Jeff R; Kent, Richard W
Abstract : Objectives: The National Highway Traffic Safety Administration and the American Academy of Pediatrics recommend children be placed in rear-facing child restraint systems (RFCRS) until at least age 2. These recommendations are based on laboratory biomechanical tests and field data analyses. Due to concerns raised by an independent researcher, we re-evaluated the field evidence in favour of RFCRS using the National Automotive Sampling System Crashworthiness Data System (NASS-CDS) database. Methods: Children aged 0 or 1 year old (0–23 months) riding in either rear-facing or forward-facing child restraint systems (FFCRS) were selected from the NASS-CDS database, and injury rates were compared by seat orientation using survey-weighted χ 2 tests. In order to compare with previous work, we analysed NASS-CDS years 1988–2003, and then updated the analyses to include all available data using NASS-CDS years 1988–2015. Results: Years 1988–2015 of NASS-CDS contained 1107 children aged 0 or 1 year old meeting inclusion criteria, with 47 of these children sustaining injuries with Injury Severity Score of at least 9. Both 0-year-old and 1-year-old children in RFCRS had lower rates of injury than children in FFCRS, but the available sample size was too small for reasonable statistical power or to allow meaningful regression controlling for covariates. Conclusions: Non-US field data and laboratory tests support the recommendation that children be kept in RFCRS for as long as possible, but the US NASS-CDS field data are too limited to serve as a strong statistical basis for these recommendations.